Validation of the Slovenian version of short sense of coherence questionnaire (SOC-13) in multiple sclerosis patients - Stern Biljana; Socan Gregor; Rener-Sitar Ksenija; Kukec Andreja; Zaletel-Kragelj Lijana (Sciendo, 2019)
To validate the Slovenian version (SOC-13-SVN) of Sense of Coherence 13-item instrument (SOC-13) in Slovenian multiple sclerosis (MS) patients.